Motivation and engagement in various learning environments : interdisciplinary perspectives - Thomson, Margareta M., 1971- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"The current volume includes research studies from different domains related to students' motivation, engagement and learning, parents' experiences, and teachers' involvement with novel interdisciplinary programs. A variety of perspectives are presented in this collection of work, namely students' views, teachers 'experiences, and parents' attitudes. The current volume compiles research on motivation and engagement in various domains, such as Science Technology Engineering and Mathematics (STEM), Literacy, Design and Computer Science. A particular focus is placed on interdisciplinarity, as learning occurs across multiple domains, and in various contexts, such as formal informal education. Additionally, the current volume provides examples of studies discussing different modalities in designing and implementing innovative educational programs, inquiry-based learning, and useful applications for instruction. The volume appeals to a wide audience, including researchers, teachers, parents, students, and education specialists"--